Dynamics of q-Deformed Logistic Map via Superior Approach - Renu; Ashish; Chugh, Renu (Journal of Applied Nonlinear Dynamics, 2026)
Inspired by various studies on q-deformations in physical systems and their wider applications in different fields, we study the q-deformed logistic map via a superior fixed-point feedback approach. Different dynamical characteristics such as fixed-points, time-series evolution, period-doubling bifurcation, and Lyapunov exponent of the system are analyzed using a superior approach. The results are carried out analytically as well as experimentally. Under the proposed approach, due to the presence of an additional control parameter α, the system exhibits superior dynamical characteristics such as better stability range, suitable lower maximum Lyapunov exponent value, and an improved sensitivity as compared to the traditional approach.